Предмет: Математика,
автор: Аноним
3) 0,125a⁹- 0,15a⁶b⁴ +0,06a³b⁸ - 0,008 b¹²;
Ответы
Автор ответа:
2
Это куб разности двух выражений.
Решаем по формуле: a³ - 3a²b + 3ab² - b³ = (a - b)³
0,125a⁹- 0,15a⁶b⁴ +0,06a³b⁸ - 0,008 b¹² =
= (0,5a³)³ - 3 · 0,25a⁶ · 0,2b⁴ + 3 · 0,5a³ · 0,04b⁸ - (0,2b⁴)³ =
= (0,5a³ - 0,2b⁴)³
Ответ: (0,5a³ - 0,2b⁴)³
Похожие вопросы
Предмет: Математика,
автор: pcheremnykh
Предмет: Физика,
автор: grisha090101
Предмет: Математика,
автор: krasavina07
Предмет: Физика,
автор: prutik24
Предмет: Алгебра,
автор: adelina139